The future of the peasant rondas - Flórez, David (2002)
The success of the Peruvian peasant patrols in the fight against subversion or as a result of a more autonomous local process of rural populations in combating rustling and other forms of external aggression has been widely documented in contemporary literature (see, among others, , Churats et al., 2001, Degregori et al., 1996, Guerrero Bravo 2001, Hernández 2000, Yrigoyen 2001). This success, together with the social breadth of the movement and its way of operating in areas supposedly reserved for urban political instances, has even led some authors to propose the Peruvian peasant patrols as "some of the most vital new ways of doing politics in the planet" (Starn 1992).